Optimization of hydrogen and syngas production from PKS gasification by using coal bottom ash - Shahbaz, M. (Elsevier Ltd, 2017)
Catalytic steam gasification of palm kernel shell is investigated to optimize operating parameters for hydrogen and syngas production using TGA-MS setup. RSM is used for experimental design and evaluating the effect of temperature, particle size, CaO/biomass ratio, and coal bottom ash wt on hydrogen and syngas. Hydrogen production appears highly sensitive to all factors, especially temperature and coal bottom ash wt. In case of syngas, the order of parametric influence is: CaO/biomass > coal bottom ash wt > temperature > particle size. The significant catalytic effect of coal bottom ash is due to the presence of Fe2O3, MgO, Al2O3, and CaO. A temperature of 692 °C, coal bottom ash wt of 0.07, CaO/biomass of 1.42, and particle size of 0.75 mm are the optimum conditions for augmented yield of hydrogen and syngas. The production of hydrogen and syngas is 1.5 higher in the pilot scale gasifier as compared to TGA-MS setup. © 2017 Elsevier Ltd